Motor vehicles act, 1939 - Mallick, M.R (Calcutta, 1985)
MOTOR VEHICLES ACT, 1939 as amended from time to time is an important Central Legislation. Broadly, the Act can be divided in three parts. The first part deals with the matter of granting licences to drivers etc. and permits to the owners of motor vehicles. As permit has been held to be a right in property, the grant and refusal of permit and cancellation of permit have generated lots of disputes and there are plethora of decisions of the different High Courts and of the Supreme Court in these matters. The grant and refusal of permit is subject to appeal before the State Transport Appellate Tribunal. The transport authorities are also subject to the writ jurisdiction of the High Court. All these matters have been very carefully dealt with in this new commentary. The second part deals with payment of compensation 10 the victims of motor accidents. Street accidents are alarmingly on the increase. There is compulsory insurance for all motor vehicles and the claim against the owner up to a certain monetary limit is to be indemnified by the insurer. Liability of the insurer vis-a-vis the owner of the vehicle in cases arising out of motor accident claims has been crystallised by the decisions of the Supreme Court and of the various High Courts. In this commentary there are detailed discussions supported by the authoritative decisions of the Supreme Court and various High Courts as regards the liability of the owner and insu rer of the motor vehicle. Illustrative cases of award of compensation have been enumerated to help both the lawyers as well as the Claims Tribunals in arriving at a proper decision for passing award of just compensation in motor accident claim cases. The Motor Vehicles Amendment Act, 1982 has intro duced for the first time the provision for payment of compensation on no fault liability. Whether the driver of the motor vehicle is guilty of negligence or not, the claimant is entitled to obtain compensation up to a certain limit both for death or bodily injury. Claims awarded under this provision contain ed in Chapter VII A have to be promptly distributed. It is a very salutary principle for payment of compensation introduced in the Act which will go a long way to ameliorate to a certain extent financially the victims of motor accidents as quickly as possible. The third part of the Act is the criminal 5 liability arising out of the breach of the various provisions of the Motor Vehicles Act. These provisions have also been elaborately dealt with in this commentary.
Keywords: "Motor vehicles act, 1939"